Contribution of the Hair Follicular Pathway to Total Skin Permeation of Topically Applied and Exposed Chemicals - Fadli Mohd; Hiroaki Todo; Masato Yoshimoto; Eddy Yusuf; Kenji Sugibayashi (MDPI AG, 2016)
Generally, the blood and skin concentration profiles and steady-state skin concentration of topically applied or exposed chemicals can be calculated from the in vitro skin permeation profile. However, these calculation methods are particularly applicable to chemicals for which the main pathway is via the stratum corneum. If the contribution of hair follicles to the total skin permeation of chemicals can be obtained in detail, their blood and skin concentrations can be more precisely predicted. In the present study, the contribution of the hair follicle pathway to the skin permeation of topically applied or exposed chemicals was calculated from the difference between their permeability coefficients through skin with and without hair follicle plugging, using an in vitro skin permeation experiment. The obtained results reveal that the contribution of the hair follicle pathway can be predicted by using the chemicals' lipophilicity. For hydrophilic chemicals (logarithm of n-octanol/water partition coefficient (log Ko/w) < 0), a greater reduction of permeation due to hair follicle plugging was observed than for lipophilic chemicals (log Ko/w ≥ 0). In addition, the ratio of this reduction was decreased with an increase in log Ko/w. This consideration of the hair follicle pathway would be helpful to investigate the efficacy and safety of chemicals after topical application or exposure to them because skin permeation and disposition should vary among skins in different body sites due to differences in the density of hair follicles.